BERAS ANALOG BERBAHAN DASAR TEPUNG UBI UNGU FORTIFIKASI TEPUNG TEMPE SEBAGAI DIVERSIFIKASI MAKANAN POKOK NON BERAS - Nurjanah, Nunung; Wahyuni, Wiwik; Wibowo, Nunuk Lismonika (Journal of Food Technology and Agroindustry dipublikasikan oleh Universitas Wiraraja, 2024)
Analog rice made from purple yam flour fortified with tempeh flour was made with the aim of diversifying non-rice staple foods and as an innovation of processed purple yam and tempeh.This study was a randomized controlled design (CRD)with a variable ratio ratio between purple sweet potato flour and tempeh flour (65%:35%, 75%:25%, 85%:15%) which was repeated twice. Parameters observed were physical characteristics, namely swelling power, chemical properties, namely carbohydrate, protein, anthocyanin and glycemic index content. This study used ANOVA and DMRT analysis. The results of the analysis showed that there were significant differences in the ability of swelling power, carbohydrate, protein, anthocyanin and glycemic index content. The highest swelling power ability is found in analog rice with a ratio of purple yam flour and tempeh flour 85%: 15% and the lowest is in a ratio of 65%: 35%. The highest carbohydrate is found at a ratio of 85%: 15%. On the other hand, analogous rice with purple yam flour and tempeh flour which has the highest protein is found at a ratio of 65%:35%. The highest anthocyanin is found in the ratio of 85%:15%. The highest glycemic index figure is in the ratio of 85%:15%, but the glycemic index of each ratio is low, namely <55. Analog rice made from purple yam flour fortified with tempeh flour can be used as a diversification of non-rice staple foods and can be used as an alternative functional food.